Hubungan pengetahuan dan sikap dengan tindakan pencegahan demam berdarah dengue di Kelurahan Taratara Kecamatan Tomohon Barat Kota Tomohon - Gloria Kairupan; Tyrsa Monintja; Dina Rombot (UNIVERSITAS SAM RATULANGI, 2026)
Background: Dengue Hemorrhagic Fever (DHF) is a disease transmitted by the Aedes aegypti mosquito and is still a health problem in Taratara Village, which in 2024 recorded 115 cases. Community knowledge and attitudes play a role in shaping preventive measures. Objective: To determine the relationship between knowledge and attitudes with dengue prevention measures in Taratara Village, West Tomohon District. Aim: To determine the relationship between knowledge and attitudes with dengue prevention measures in Taratara Village, West Tomohon District. Methods: This study used a quantitative analytical design with a cross-sectional approach. The sample amounted to 95 respondents who were selected through purposive sampling. Data was collected using a questionnaire and analyzed using the Chi-Square test. Results: The majority of respondents had good knowledge (80%) and good attitudes (55.8%). However, most showed poor preventive measures (62.1%). The bivariate test showed no significant relationship between knowledge and action (p = 0.139) or between attitude and action (p = 0.415). Conclusion: The knowledge and attitude of the community is relatively good, but optimal dengue prevention measures have not been followed. Increased environmental support and community-based pemberantasan sarang nyamuk activities are needed.